Tension Bullae With Peripheral Pneumothorax - Tushar Bajaj MD; Bushra Malik MS; Sudhagar Thangarasu MD, FACP (SAGE Publishing, 2020)
The differentiation between tension bullae, chronic tension pneumothorax, and atypical pneumothorax is difficult just from history and physical examination alone. A chest X-ray may help determine the underlying etiology; however, further imaging with computed tomography in stable patients may be necessary for accurate assessment of size, number, and location before considering any interventions. In this article, we present a rare case report of tension bullae with peripheral pneumothorax and recommend against needle thoracostomy in stable patients with tension bullae in order to obtain further imaging that may result in a change in the standard management.